The invisible ones - Penney, Stef (G.P. Putnam's Sons, 2012)
Hovering between paralysis and delirium in a hospital bed, half-Romany private investigator Ray Lovell evaluates a case involving the missing wife of a charismatic traveling Gypsy whose hostile family is hiding a tragic secret.